Sistema de gest??o integrado: a rela????o entre os diferentes tipos de integra????o e dificuldades na gest??o e opera????o - Gon??alves, Alexandre Costa (2015)
Organizations that have more than one management system deployed face difficulties in integrating or maintenance of these systems, this study sought to attain the goal of the verification and analysis of the difficulties in the management and operation of integrated management systems and their relationship with the different levels of integration raised in the bibliography. The methodology used qualitative oriented research by means of a semi-structured interview with 21 issues applied in integrated management systems experts and through a quantitative Survey of 35 questions for an approach in groups of managers of various hierarchical levels (strategic, tactical, and operational). The results have been an offshoot of the systems integration levels of deployment for the maintenance, the levels proposed by the authors review arrived at the most four levels, and in this research were found up to five levels of integration for the maintenance of the systems, which are the non-integrated, interconnected, the combined, the semi-integrado and the fully integrated as well as the connection of these levels of integration with the problems proposed in the survey, that is, the proof that the higher the level of integration are the difficulties of the management and operation of the integrated management system. The research gives his contribution to organizations that have more than two certifications, to point out the possible developments of their systems and management difficulties and operation related to each type of integration. To the Academy the contribution this on attesting the evolution of four possible levels of integration during deployment to five or more on system maintenance.